An unusual cause of orthopnoea-hashimoto's thyroiditis presenting as bilateral diaphragmatic palsy. (2017) - Thulaseedharan, N.K.; Geetha, P.; Arathi, N.; Shameer, V.K.; Jayachandran, N.V.; Subramaniam, Gomathy; Narayanan, Santhosh
Abstract: We report a case of 36 yr old male without any comorbidities, who presented with a history of gradually progressive dyspnoea and orthopnoea for 6 months. Physical examination revealed bradycardia, paradoxical respiration suggestive of bilateral diaphragmatic palsy. Fluoroscopy demonstrated the presence of bilateral diaphragmatic paralysis. Etiological work up showed evidence of autoimmune hypothyroidism due to hashimoto's thyroiditis. Other possibilities were ruled out with appropriate tests. He was started on thyroxine and showed symptomatic improvement.